Optimization of Time and Air Flow Speed of Densitometric Table Machine (Sutton) Towards the Efficiency of Separation of Arabica Coffee Beans Ready for Export - Daffa Alfinsyah; Andi Setiawan; Desi Sri Pasca Sari Sembiring (INFOKUM, 2026)
The physical quality of Arabica coffee beans is a key determinant of product competitiveness in the export market. One common problem is the presence of hollow beans (trieste), which can reduce the quality and economic value of the coffee. Therefore, an effective sorting process utilizing a Sutton-type densitometric table is necessary. This study aims to analyze the effect of airflow velocity and sorting time and determine the optimal treatment combination to improve the separation performance of hollow coffee beans. This study used a factorial Randomized Block Design (RBD) with two treatment factors, namely air flow speed consisting of three levels (low, medium, and high) and sorting time consisting of three levels (1 hour, 2 hours, and 3 hours). Each treatment combination was repeated twice to obtain nine treatment combinations. The parameters observed included engine capacity, air flow stability, and the level of purity of the sorting results. Data were analyzed using analysis of variance (ANOVA) at a significance level of 5% and continued with the Duncan test. The results showed that variations in airflow velocity and sorting time had a highly significant effect (p<0.05) on all observed parameters. The best treatment combination was obtained at A3W3 (high airflow velocity with a sorting time of 3 hours), which resulted in a machine capacity of 230 kg/hour, airflow stability of 14.90, and a purity level of 100%. In general, increasing airflow velocity followed by increasing sorting time tends to increase the effectiveness of the process of separating hollow coffee beans.